2021
DOI: 10.5334/ijic.5589
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Reviews on Interprofessional Collaboration in Primary Care: Barriers and Facilitators

Abstract: Introduction: Interprofessional collaboration (IPC) is becoming more widespread in primary care due to the increasing complex needs of patients. However, its implementation can be challenging. We aimed to identify barriers and facilitators of IPC in primary care settings.Methods: An overview of reviews was carried out. Nine databases were searched, and two independent reviewers took part in review selection, data extraction and quality assessment. A thematic synthesis was carried out to highlight the main barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
88
2
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(98 citation statements)
references
References 76 publications
2
88
2
6
Order By: Relevance
“…Power imbalances between professionals were identified in a thematic synthesis as a barrier to interprofessional collaboration. 25 In the current study, dietitians described collaboration as being driven by the GP, with some experiencing good engagement and others receiving no engagement beyond the referral. Communication and competence have been identified as important in addressing power imbalances and trust.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Power imbalances between professionals were identified in a thematic synthesis as a barrier to interprofessional collaboration. 25 In the current study, dietitians described collaboration as being driven by the GP, with some experiencing good engagement and others receiving no engagement beyond the referral. Communication and competence have been identified as important in addressing power imbalances and trust.…”
Section: Discussionmentioning
confidence: 75%
“…Access to practice software facilitated collaboration in the current study, but few participants described formal processes for engaging with the care team, even when co‐located with the referring practitioner. Power imbalances between professionals were identified in a thematic synthesis as a barrier to interprofessional collaboration 25 . In the current study, dietitians described collaboration as being driven by the GP, with some experiencing good engagement and others receiving no engagement beyond the referral.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Despite the widespread agreement on the importance and promises of interdisciplinary research teams (IDRT), barriers for effective IDRT implementation remain significant. Prior studies across a wide range of academic disciplines have identified several common barriers to IDRT including (1) university organization that favors mono-disciplinary departmental structure; [26] (2) tenure and promotion system that favors individual productivity; [27] (3) additional challenges posed by distance between collaborators (e.g., time spent in transit, scheduling conflict) [28], (4) difference in cultural norms across disciplines (e.g., ranking of research journals, importance of extramural funding, teaching/clinical responsibilities) [29], and (5) lack of experience in teamwork among researchers and research administrators (effective communication, team role vs organizational hierarchy, resource sharing, contract negotiations, identifying common goals/shared mental model) [30]. Overall, it is more difficult, expensive, and time consuming to work in research teams vs. solo research [5].…”
Section: Discussionmentioning
confidence: 99%
“…So kann dem mangelnden Wissen übereinander mit berufsübergreifenden, gemeinsamen Aus-, Weiter-und Fortbildungen (Ulrich, Amstad et al 2020) entgegen gewirkt werden. Gemeinsame Arbeitsplätze (Co-Location) etwa in Primärversorgungszentren (Rawlinson, Carron et al 2021) fördern eine niedrigschwellige Änderung der Kooperationskultur. Der Austausch zwischen Professionen und Einrichtungen kann bereits jetzt durch die Möglichkeiten eines "asynchronen Informationsaustauschs" ohne die Notwendigkeit gleichzeitiger Verfügbarkeit verbessert und gefördert werden (Philipps, Scheible et al 2021).…”
Section: Konkrete Verbesserungsansätze Bereits Jetzt?unclassified